Jaringan Syaraf Tiruan Pengaruh Konsumsi Durian Pada Ibu Hamil Dengan Menggunakan Metode Backpropagation - Simatupang, Erpina (Bulletin of Data Science, 2023)
A pregnant woman is a woman who is carrying a foetus, which is the gateway to the creation of a reliable next generation. In other words, pregnant women are figures who will one day give birth to the next generation who have the skills and ability to make changes for the better. Pregnant women are also a gift for the progress of the nation because from pregnant women are born prospective successors who will lead a generation in the future. Artificial neural network, or JST for short, has the ability to learn and generate rules or operations from several examples or inputs that are entered and make predictions about possible outputs that will appear or store the characteristics of the input stored to it. Backpropagation is one method that is often used in solving complex problems because networks with this method are trained using a guided learning method. The network is given a pair of patterns consisting of the input pattern and the desired pattern. When a pattern is given to the network, the weights are changed to minimise the difference between the output pattern and the desired pattern. This training is done repeatedly so that all patterns issued by the network can fulfil the desired pattern.